Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Gaming Cultures and Place in Asia-Pacific - Hjorth, Larissa; Chan, Dean (Routledge, 2009)
This collection explores the relationship between digital gaming and its cultural context by focusing on the burgeoning Asia-Pacific region. Encompassing key locations for global gaming production and consumption such as Japan, China, and South Korea, as well as increasingly significant sites including Australia and Singapore, the region provides divergent examples of the role of gaming as a socio-cultural phenomenon. Drawing from micro ethnographic studies of specific games and gaming locales to macro political economy analyses of techno-nationalisms and trans-cultural flows, this collection provides an interdisciplinary model for thinking through the politics of gaming production, representation, and consumption in the region.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé